Exploring QSAR for Antimalarial Activities and Drug Distribution within Blood of a Series of 4-Aminoquinoline Drugs Using Genetic-MLR - Amir Najafi; Soheil Sobhanardakani; Mehdi Marjani (Journal of Chemistry)
Malaria has been one of the most significant public health problems for centuries. QSAR modeling of the antimalarial activity and blood-to-plasma concentration ratio of Chloroquine and a new series of 4-aminoquinoline derivatives were developed using genetic algorithms with multiple linear regression (GA-MLR) method. We obtained two different models against Chloroquine-sensitive (3D7) and Chloroquine-resistant (W2) strains of Plasmodium falciparum with good adjustment levels. Drug distribution in blood, defined as drug blood-to-plasma concentration ratio (Rb), is related to molecular descriptors. Leave-many-out (LMO) and Y-randomization methods confirmed the models' robustness.